2021
DOI: 10.33369/jk.v5i1.13630
|View full text |Cite
|
Sign up to set email alerts
|

Dribble Training Model Development Jump Shoot Basketball Sports Branch On Students

Abstract: This study aims to develop a dribble jump shoot training model in basketball. This type of research is research and development (Research and Development). In this development research, the product developed is a dribble jump shoot training model in basketball.The subjects in this research and development were 3 experts and 10 basketball athletes. The instruments used in this research and development were questionnaires and questionnaires used to collect data at the following stages: (1) needs analysis; (2) ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…According to Iqbal (2015), a jump shoot is a very effective shot that is difficult for opponents to block. In line with that, Wijaya (2017) argues that the jump shot is an effective shooting technique because shooting in a jumping position with the initial squatting position will be very difficult to be blocked by the opponent (Bangun et al, 2021). Based on these two opinions, it can be concluded that jumping ability in basketball is an important skill.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…According to Iqbal (2015), a jump shoot is a very effective shot that is difficult for opponents to block. In line with that, Wijaya (2017) argues that the jump shot is an effective shooting technique because shooting in a jumping position with the initial squatting position will be very difficult to be blocked by the opponent (Bangun et al, 2021). Based on these two opinions, it can be concluded that jumping ability in basketball is an important skill.…”
Section: Discussionmentioning
confidence: 95%
“…Although due to the physically demanding characteristics of basketball, players are required to perform various high-intensity actions and quick reactions in a short period during the game, such as sprinting, dribbling, shuffling, jumping, and quick change of direction (Ben Abdelkrim et al, 2010;Alemdaro lu, 2012). Therefore, physical fitness is usually considered an essential factor that determines the development of other athletic skills to a large extent.…”
Section: P = F * Smentioning
confidence: 99%
“…Pertandingan bola..basket, di wajibkan tim bisa menggabungkan serta pengaturan teknik-teknik permainan basket, teknik dasar bola basket bisa dikelompokan seperti: bola basket adalah olahraga yang aktif dan memiliki daya tarik utamanya saat melakukan gerakan memainkan bola.basket ketika melakukan lay-up, shooting, passing, dan dribble (Rizhardi, 2020). Bangun et al, (2021) dribble adalah hal yang mendasar dari teknik bola basket, tidak ada pemain dengan bola yang bisa pindah ke lapangan jika dia tidak menggiring bola. Passing berarti mengoper bola (Nuril, 2007).…”
Section: Pendahuluanunclassified
“…The deformation of technical movements directly affects the shooting percentage. 12 Therefore, we must pay attention to physical training to improve the hit rate. The shooting rate is stable and improved only with good special physical fitness as a foundation.…”
Section: Strengthened Special Physical Fitness Trainingmentioning
confidence: 99%